Applicability of cone beam computed tomography gray values for estimation of primary stability of dental implants - Sheikhi, Mahnaz; Karami, Mehdi; Abbasi, Somayeh; Moaddabi, Amirhossein; Soltani, Parisa (Brazilian Dental Science, 2020)
Objective: To evaluate the relationship between bone density measured by computed tomography (CT) and cone beam computed tomography (CBCT) (Sirona’s Galileos scanner) with primary stability of dental implants. Material and methods: 20 fresh bovine femoral heads were prepared by removal of soft tissue, sectioning of the bone, and placement of markers for location and angulation of implants. Bone density of peri-implant areas was determined preoperatively by CT and CBCT scanning of the prepared bone samples represented by Hounsfield units (HUs) and gray values (GVs), respectively. Then, 60 implants in three sizes (diameter = 4 mm, length = 8, 10, and 12 mm) were inserted into the bones and maximum insertion torque (IT) was recorded. Osstell device was also used for determining the implant stability quotient (ISQ) for each implant. Statistical analysis was performed on the data (alpha = 0.05). Results: Mean ± SD values of GV, HU, and ISQ were 1592.75 ± 231.82, 675.26 ± 115.38 and 61.90 ± 10.14, respectively. Moreover, the most frequent IT limit was 30-35 Ncm (41.4%). Significant relationships were observed between HU and IT, GV and IT, HU and ISQ, GV and ISQ, and IT and ISQ in all implant sizes. Moreover, GV and HU also significantly correlated to each other. Conclusion: Bone density values in CBCT and CT scans are positively associated to primary stability of dental implants. Therefore, GVs obtained from Galileos CBCT scanner can be used for preoperative selection of edentulous sites which allow for better implant stability or locations which require further procedures for enhancing the success rate of dental implants. KEYWORDS Computed tomography; Cone beam computed tomography; Dental implant.